Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1093/oxfordjournals.aje.a113129
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Proportions of Swimmers Among Well Controls and Children With Enterovirus-Like Illness Shedding or Not Shedding an Enterovirus

Abstract: CHildren between the ages of less than 1 year and 15 years who visited a pediatric clinic in Madison, Wisconsin, from June 13 through September 1, 1977, were surveyed for the frequency and location of swimming they had done in the two weeks prior to the clinic visit. The study population consisted of 679 well controls, and 296 children with enteroviral-like syndromes. Throat and rectal swab specimens were collected from 241 of the ill patients and from 27 well children. Non-polio enteroviruses were recovered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Polioviruses, coxsackievirus A and B, and echoviruses have been found in rivers (e.g., Payment et al, 1988;Miyama et al, 1992;Tani et al, 1995), but coxsackievirus A and B and echoviruses have also been reported in lakes (D'Alessio et al, 1981) and swimming pools (Kee et al, 1994). Sources of waterborne enteroviruses suggested in the scientific literature include sewage (Oostvort et al, 1994;Van der Avoort et al, 1995), storm sewer discharge and runoff (D'Alessio et al, 1981), human activities (Payment et al, 1988;Kee et al, 1994), and diapers and sullage (Field et al, 1968).…”
Section: Occurrencementioning
confidence: 99%
See 4 more Smart Citations
“…Polioviruses, coxsackievirus A and B, and echoviruses have been found in rivers (e.g., Payment et al, 1988;Miyama et al, 1992;Tani et al, 1995), but coxsackievirus A and B and echoviruses have also been reported in lakes (D'Alessio et al, 1981) and swimming pools (Kee et al, 1994). Sources of waterborne enteroviruses suggested in the scientific literature include sewage (Oostvort et al, 1994;Van der Avoort et al, 1995), storm sewer discharge and runoff (D'Alessio et al, 1981), human activities (Payment et al, 1988;Kee et al, 1994), and diapers and sullage (Field et al, 1968).…”
Section: Occurrencementioning
confidence: 99%
“…The symptoms included headache, fever, vomiting, abdominal cramps, diarrhea, unspecified gastrointestinal symptoms, and pharyngitis (Hawley et al, 1973;D'Alessio et al, 1981;Kee et al, 1994). Danes et al (1983) stated that there was a high incidence of enteroviral infections among children aged 5-16 years, but did not provide data for the incidence to be calculated.…”
Section: Qualitative Datamentioning
confidence: 99%
See 3 more Smart Citations